Analysis the Influence of Audit Committee Characteristics on Tax Aggressiveness in Indonesia - Budi Harsono; Sherina Yoren (Universitas Muhammadiyah Makassar, 2022)
This research seeks to examine the impact between the intend of corporate tax aggressive with several characteristics of audit committee members, namely independence, expertise, diligence and gender diversity. Measurement of effective tax rate paid is used to measure tax aggressiveness. This study is an empirical examination of quantitative method research involving 1,632 sample data from 408 companies listed in Indonesia Stock Exchange (IDX) using time series collection within a period of 5 years (2017-2021). The method of analysis in this study is panel regression analysis and using Eviews10 and SPSS v25.0 for the data processing. The author finds that the independence of the audit committee tends to give a significant effect on tax aggressiveness. Meanwhile, the expertise, diligence, and gender diversity of the audit committee do not have a significant effect on the practice of tax aggressiveness. If shareholders, investors, and tax agents are aware of the audit committee's makeup, it may warn them of the dangers of the company's aggressive tax planning.